18F-FP-PEG2-β-Glu-RGD2: A Symmetric Integrin αvβ3-Targeting Radiotracer for Tumor PET Imaging. - Kongzhen Hu; Xiaolan Tang; Ganghua Tang; Shaobo Yao; Baoguo Yao; Hongliang Wang; Dahong Nie; Xiang Liang; Caihua Tang; Shanzhen He (PLoS ONE, 2015)
Radiolabeled cyclic arginine-glycine-aspartic (RGD) peptides can be used for noninvasive determination of integrin αvβ3 expression in tumors. In this study, we performed radiosynthesis and biological evaluation of a new 18F-labeled RGD homodimeric peptide with one 8-amino-3,6-dioxaoctanoic acid (PEG2) linker on the glutamate β-amino group (18F-FP-PEG2-β-Glu-RGD2) as a symmetric PET tracer for tumor imaging. Biodistribution studies showed that radioactivity of 18F-FP-PEG2-β-Glu-RGD2 was rapidly cleared from blood by predominately renal excretion. MicroPET-CT imaging with 18F-FP-PEG2-β-Glu-RGD2 revealed high tumor contrast and low background in A549 human lung adenocarcinoma-bearing mouse models, PC-3 prostate cancer-bearing mouse models, and orthotopic transplanted C6 brain glioma models. 18F-FP-PEG2-β-Glu-RGD2 exhibited good stability in vitro and in vivo. The results suggest that this tracer is a potential PET tracer for tumor imaging.